Patient safety incidents associated with obesity: a review of reports to the National Patient Safety Agency and recommendations for hospital practice. Issue 1032 (25th July 2011) - Booth, C M A; Moore, C E; Eddleston, J; Sharman, M; Atkinson, D; Moore, J A
Abstract : Background: The incidence and prevalence of obesity are increasing world wide. In the UK, obesity governmental strategy has primarily focused on prevention measures, with less focus on the demands of treating obese patients in hospital. Increasing service demand by obese patients coupled with a lack of adequate provision for care of these patients may lead to an increase in patient safety incidents. By classifying patient safety incidents associated with obesity reported to the National Patient Safety Agency, this report aims to identify areas for improvement in the quality and safety of care of the obese patient Methods: A search of the National Reporting and Learning System database was conducted for all incidents caused by or relating to obesity for the period 1 January 2005 to 31 August 2008. The keywords 'obesity', 'overweight', 'BMI' (body mass index), and 'bariatric' were used. The relevant free text fields of the resulting set of incidents were then searched for the terms designed to isolate incidents occurring in anaesthesia, critical care, and surgery. Reported incidents were analysed and subsequently categorised to identify incident themes. Levels of harm were also established. Results: 555 patient safety incidents were identified; 388 met inclusion criteria for analysis. 148 incidents were related to assessment, diagnosis or treatment, 213 related to infrastructure and 27 related to staffing. The majority of incidents were classified as no or low harm. Three deaths were reported, all within the domain of anaesthesia. Conclusions: This report identifies that the majority of safety incidents associated with obesity were related to infrastructure, suggesting that there is inadequate provision in place for the care of obese patients. While levels of harm were mostly low, the occurrence of incidents resulting in severe harm or death highlights the specific dangers associated with the care of the obese patient. A global approach to improving the safety of care delivery for obese patients is recommended, including obesity specific training, management structures, care pathways, and equipment provisioning.Further planning and development of operation policies is needed to ensure the safe delivery of healthcare to obese patients in the future.